SYSTEMATIC LITERATUR REVIEW MODUL MATEMATIKA UNTUK PEMBELAJARAN SECARA DARING - Putra, Aan; Sustipa, Widya (Lentera: Jurnal Ilmiah Kependidikan, 2021)
Innovation in learning is indispensable. One of the innovations that can be done is through teaching material. teaching material can be used to create motivation of the students so that they can finally improve learning outcomes. This study aims to conduct literature study related to the development of development of math modules for online learning. The research method chosen in this study is an SLR (Systematic Literature Review) method. Data collection is conducted by articles that have similar research on this research report. The article used in this study as many as 33 National Journal articles accredited from Google Scholar. Based on this study, the development of math modules for online learning can improve the ability to understand the concepts, learning outcomes and learning skills of students. Based on the literature study performed by development of math modules for online learning SMP/MTs